A physiologically based model for denitrogenation kinetics - Katz, Ira; Murdock, Jacqueline; Palgen, Marc; Farjot, Géraldine (Medical gas research, 2017)
Under normal conditions we continuously breathe 78% nitrogen (N2) such that the body tissues and fluids are saturated with dissolved N2. For normobaric medical gas administration at high concentrations, the N2 concentration must be less than that in the ambient atmosphere; therefore, nitrogen will begin to be released by the body tissues. There is a need to estimate the time needed for denitrogenation in the planning of surgical procedures. In this paper we will describe the application of a physiologically based pharmacokinetic model to denitrogenation kinetics. The results are compared to the data resulting from experiments in the literature that measured the end tidal N2 concentration while breathing 100% oxygen in the form of moderately rapid and slow compartment time constants. It is shown that the model is in general agreement with published experimental data. Correlations for denitrogenation as a function of subject weight are provided.